Ogan Ilir District Waste Transportation Cost Calculation Model Using an Engineering Economics Approach - Akhirini, Akhirini; Firda, Ani; Permatasari, Rosmalinda; Bethary, Rindu Twidi (JURUSAN TEKNIK SIPIL, 2024)
One issue that might lead to environmental disturbances in Indonesia's varied areas is solid waste. It is possible to execute waste management effectively, and one such implementation is the installation of waste transportation. If waste transportation fleet is unable to handle the current waste generation, which may result in waste accumulation, then the problem of transporting waste may arise. In order to address this issue, assistance is required in the form of waste transportation costs. In accordance with the local conditions at the time of the study, this paper analyzes the calculation of waste transportation fees. The collection of information was done to determine how waste transportation was currently operating, including the number of vehicles, the distance that went, their rotation, and their carrying capacity. According to the study's findings, the cost of garbage transportation is Rp. 3,277/km or Rp. 21,257/m3 for armroll trucks and Rp. 5,980/km or Rp. 86,459/m3 for dump trucks. These findings show that the fee for Armroll trucks is higher than the levy for dump trucks. This is because Armroll vehicles have a longer service route and use more fuel.